Service Life Assessment and Safety Inspection of Pressure Vessels: A Comprehensive Analysis of Structural Integrity and Performance - Adi Ganda Putra; Muhammad Prima Andika Putra; Matijanti Matijanti; Pawawoi Pawawoi (Journal of Technology and Engineering, 2026)
Pressure vessel is a container used to store fluids and is very necessary for various industrial activities. Fluids stored in pressure vessels are fluids that have special characteristics and treatment, such as fluids at low or high temperatures, pressurized fluids and so on. In general, a pressure vessel is a container made of metal. Materials that contain metal will definitely experience corrosion. Corrosion can occur, one of the reasons is because there is a chemical reaction on the metal surface caused by the low pH of the water and humid air, so that the metal becomes thinner over time. This will affect the strength of the metal to withstand pressure. The thinner the metal, the less pressure it can withstand. With corrosion, the pressure vessel's ability to withstand pressure will decrease. If the pressure held is higher than the capacity of the pressure vessel, it can cause work accidents. This research will analyze the service life of pressure vessels using inspection procedures based on Minister of Manpower Regulation Number 37 of 2016 concerning Occupational Safety and Health of Pressure Vessels and Storage Tanks. To calculate the effect of thickness on the pressure of the pressure vessel, it will be based on the formula obtained from ASME sec VIII, div.1 regarding boilers and pressure vessels. The pressure vessel that will be tested is of the Jiangsu Ashun brand at PT. Setia Gas Jaya. From the results of analysis and testing, it shows that the pressure vessels at PT. Setia Gas Jaya has the point that experiences the most corrosion, namely at the bottom-head, which was originally 6.8 mm to 6.62 mm after 2 years and 3 months of operation. The results of the analysis also show that with a working pressure of 3.3 MPa, the pressure vessel can be operational for 13 years 3 months 13 days, or its remaining useful life is 11 years 13 days starting from June 2023.